Odpowiedzi

  • Użytkownik Zadane
2010-03-07T18:46:45+01:00
A)
{ 2x + y = 4
{ x - y = 5
________________
2x+y+x-y=4+5
3x=9/:3
x=3

{x=3
{3-y=5
{x=3
{-y=5-3
{x=3
{-y=2/:(-1)
{x=3
{y=-2
2010-03-07T18:49:21+01:00
A) { 2x + y = 4
{ x - y = 5
2x+y=4
x=y+4
2(y+4) + y=4
x=y=4
2y+8+y=4
x=y+4
3y=-4/3
x=y+4
y=-4/3
x=-4/3 + 4
y=-4/3
x=8/3
Najlepsza Odpowiedź!
2010-03-07T18:56:13+01:00
A) { 2x + y = 4
{ x - y = 5

2x+y=4
x=5+y

2(5+y)+y=4
x=5+y

10+2y+y=4
x=5+y

3y=-6 /:3
x=5+y

y=-2
x=7
b) { 3x - 5/4 y = -7 /*4
{ 0,2x + 8/5 y = 13 /*5

12x-5y=-28
x+8y=65

12x-5y=-28
x=65-8y

12(65-8y)-5y=-28
x=65-8y

780-96y-5y=-28
x=65-8y

-101y=-808 /:(-101)
x=65-8y

y=8
x=65-64

x=1
y=8
c) { 2 - (x-y)/3 = (x+y)/7 /*21
{ (y-x)/4 + 3/2 y = 2,25 /*4

41-7x+7y=x+y
-x+y+6y=9

-7x-x+7y-y=-41
-x+7y=9 /*(-1)

-8x+6y=-41
x-7y=-9

-8x+6y=-41
x=-9+7y

-8(-9+7y)+6y=-41
x=-9+7y

72-56y+6y=-41
x=-9+7y

-50y=-111 /:(-50)
x=-9+7y

y=2,22
x=-9+7*2,22

x=6,54
y=2,22
d) { (x-1) (x + 1) - x² = 2 - x - y
{ (x-1)² + (y+1)² - x² + y²

x²+x-x-1-x²=2-x-y
x²-1+y²+1-x²+y²
W tym przykładzie nie wiem gdzie jest = w II równaniu

Mam nadzieje, że pomogłam
Pozdrawiam!!!